Practical determination of HVAC – HVDC Hybridization ratio for Offshore Transmission network Architectures through technico-economic considerations. Issue 27 (2016) - Roses, Adrià Pibernat; Francois, Bruno
Abstract: Transmission network architectures between an offshore wind farm and the grid in shore are analyzed. Models of HVAC, HVDC and hybrid transmission systems are developed in order to determine losses, costs and voltage drops according to the offshore distance and the transmitted power. An optimization framework is presented to order required calculation subroutines and process technico-economic analysis. The optimal hybridization ratio to set the power transfer between HVDC and HVAC transmission networks is then found. For comparisons, the connection of 300 MW offshore wind farm with a 100 km distance is studied.